Spectrum of endometrial lesions observed on histopathological examination of endometrial samples in women with abnormal uterine bleeding - Dwivedi, Smriti S.; Bajpai, Malay; Bhushan, Indu; Satkirti, Arunima (International Journal of Research in Medical Sciences, 2019)
Background: Abnormal uterine bleeding is one of the common gynecological complaints of women of all age groups. Histopathological study of endometrial biopsy and curettage samples is an effective diagnostic modality that can be used to identify cause of AUB at its earliest. This study was done to investigate the various endometrial causes of AUB that frequently come to our hospital and their incidence in various age groups i.e. reproductive, perimenopausal and postmenopausal. Methods: This study was conducted on 108 patients who clinically presented with AUB and had their endometrial biopsy and curettage specimens sent to the histopathology department of our tertiary care hospital and teaching centre, located in Uttar Pradesh from June 2018 to May 2019. The endometrial patterns were observed, and their frequencies and percentages were computed and classified age group wise. Results: These studies included patients with age range from 19 to 77 years. The predominant age group with AUB was reproductive age group (<40 years). The most common histopathological finding in this study was normal menstrual pattern (48.15 %). The endometrial pathologies observed were hormonal imbalance and pill effect (22.22%), atrophic endometrium (10.19%), chronic endometritis (5.56%), benign endometrial polyp (4.63%), gestation products (3.70%), endometrial hyperplasia (3.70%), and endometrial carcinoma (1.85%). Conclusion: The most commonly known cause of AUB in reproductive age group is due to hormonal imbalance. Endometrial hyperplasia and carcinoma are usually more common in the perimenopausal and postmenopausal age groups. Overall, in patients with no organic cause of AUB, normal cyclical endometrial pattern is the most prevalent endometrial pattern observed. Conclusions: The most commonly known cause of AUB in reproductive age group is due to hormonal imbalance. Endometrial hyperplasia and carcinoma are usually more common in the perimenopausal and postmenopausal age groups. Overall, in patients with no organic cause of AUB, normal cyclical endometrial pattern is the most prevalent endometrial pattern observed.